Rio de Janeiro as a smart city: citizenship and participation in “polisdigitocracy” - Castro, Paulo César (2019)
Rio de Janeiro was elected in 2013 as the “Smart City of the Year” by the Smart City Expo World Congress, a fair held in Barcelona. The capital of the state of Rio de Janeiro was highlighted with the project Gestão de Alto Desempenho (High Performance Management) which includes the subproject Centro de Operações Rio (COR – Rio Operations Center). COR is a monitoring center that has 1,500 video cameras and analyzes data received in real time from several technological sensors scattered throughout the city. This is the result of an agreement between the city hall and several technology companies. The initiative is supported as part of the belief in a model of “polisdigitocracy”, a word that, according to former Mayor Eduardo Paes, means the digital version of Greek democracy for cities in the 21st century. This article is based on an ongoing investigation. It intends to evaluate —through discourses of the actors directly involved in the project— how the idea of smart city in Rio was put into practice. The research aims to analyze if technology is being used as another strategy for the city to have its destiny defined by the experts or if the word “intelligence” also includes the knowledge of the residents.